Supraorbital Keyhole Approach to Upper Basilar Artery Aneurysms via the Optico-Carotid Window: A Cadaveric Anatomic Study and Preliminary Application - Ma, Y.; Lan, Q. (min - Minimally Invasive Neurosurgery, 2011)
No anatomic data are available addressing the surgical indication for upper BA aneurysms via the supraorbital keyhole approach (SOKA).An anatomic study of the SOKA to the upper BA via the optico-carotid window (OCW) was designed. Our clinical experience is reported.After completing the SOKA craniotomy on 8 cadaveric heads, the width and length of OCW and the length of the supraclinoid internal carotid artery (SCICA) were measured. Measurement of the following was carried out through the OCW: (i) linear distance (a) of the BA from the most proximal point of visualization of the BA to the posterior clinoid process level, (ii) perpendicular distance (b) from the most distal point of visualization along the elongation of the BA to the anterior fossa level. After posterior clinoidectomy and orbitectomy, the measurement of (a) and (b) was repeated.The width and length of OCW and the SCICA length were 7.6±2.1 mm, 11.6±2.3 mm, and 12.7±2.4 mm. The distance (a) was 5.0±1.2 mm, increased by 3.4±1.0 mm after posterior clinoidectomy. The distance (b) was 12.8±2.6 mm, increased by 3.3±1.2 mm after orbitectomy. 9 aneurysms were completely clipped.When the width and length of the OCW are > 5 mm and > 7 mm, respectively, the SOKA can meet the requirement of exposure and manipulation of the upper BA. The upper BA aneurysms located < 10 mm higher than the anterior fossa and not more than 5 mm lower than the PCP can be treated via the SOKA. Posterior clinoidectomy and orbitectomy can increase the proximal and the distal exposure of the BA, respectively.
Keywords: microanatomy; optico-carotid window; supraorbital keyhole approach; upper basilar aneurysm